Kaji Eksperimental Peredam Dinamik dan Energy Harvesting pada Sistem Pegas Massa dengan DVA Tipe Dual Strip - Dewa Anom Pasmadi; Asnawi Lubis; Zulhendri Hasymi; Novri Tanti (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2020)
A vibrating system can be suppressed using a vibration damper. One type of vibration dampers is the dynamic vibration absorber (DVA) which usually consists of a mass spring system. In this study DVA of dual strip type is used, which are two strips connected by a spring which are attached by a pin to the main structure. The main structure being tested consists of a mass that has wheels with springs on the left and right. The vibrations that occur in dual-strip DVA is used for energy harvesting using a bimorph piezoelectric type that is attached to a dual-strip DVA. In this study the effectiveness of dual strip DVA in reducing the amplitude of the main structure is observed by varying the spring position connecting the dual strip DVA, and determining the output voltage that can be generated by piezoelectricity. From this study it was found that the effectiveness of dynamic dampers and energy harvesting were obtained for the spring position at the end of the dual strip DVA . The amplitude of the main structure can be reduced by while the output voltage generated by piezoelectric is